A LITERATURE REVIEW OF USING COMPRESSION TECHNIQUES FOR THE MANAGEMENT OF LYMPHOEDEMA (International Journal of Physiotherapy, 2018)
Background: Lymphoedema is generally defined as the formation of fluid or fluid retention causing swelling. It can be divided into primary or secondary lymphoedema based on its cause, as well as into three stages based on its pathology and severity of occurrence. Breast cancer among women is considered as the main cause of lymphoedema, but the condition occurs in both men and women.Objective: To provide a comprehensive, up-to-date literature review of lymphoedema management and the effect of compression therapy on lymphoedema reduction.Methods: A literature review was conducted utilizing the following databases PubMed, Medline, PEDro, and Science Direct.Results: The current evidence supports the use of compression therapy for lymphoedema reduction, but its mechanism of action is still not well understood.Conclusion: Although many studies recommend the use of compression therapy as an effective method for treating lymphoedema in both stages, the optimum treatment methods for lymphoedema are still unknown.